Geology, petrography and mineralogy of explosive breccias of Sallanlatva, Kola Region - Sidorov, M. Yu.; Kozlov, E. N.; Fomina, E. N. (2021)
The Sallanlatva massif belongs to the group of Paleozoic alkaline-ultrabasic complexes wide spread in the Kola Region (the northwestern part of the Fennoscandian Shield). In the central part of this massif, the host ijolite and urtites contain calcite, ankerite, ankerite-dolomite and siderite carbonatites. The explosive processes that led to the formation of carbonatite breccias in the calcite and ankerite-dolomite carbonatites occurred in Sallanlatva massife in the last stages of the carbonatite magmatism. There are two types of explosive carbonatite breccias in the Sallanlatva massif: (1) glimmerite-calciocarbonatite breccias, and (2) siderite-dolomite breccias. Analysis of the mineral composition of fragments and matrix and the shape of fragments in breccias has shown that the first material to intrude into the host calcite and ankerite-dolomite carbonatites was calcite melt. After that, dolomite melt penetrated through the fracture zones, which resulted in the formation of siderite-dolomite breccias. The differences in the mineral composition of the breccia matrix suggest that the residual carbonatite melts originate from separate magma chambers. The chamber with calcite melt was located at great depth, and some captured glimmerite fragments were abraded during the melt upwelling. Silicate-dolomite melts lifted from a shallower depth; the captured fragments of siderite carbonatites retained their angular shape. Late hydrothermal processes yielded veins and caverns with Ba-Sr-P-S-Ti-REE mineralization in the breccias and host rocks. Массив Салланлатва принадлежит к группе палеозойских щелочно-ультраосновных комплексов, широко проявленных в пределах Кольского региона (северо-западная часть Фенноскандинавского щита). В центральной части этого массива среди ийолитов и уртитов находятся крупные тела кальцитовых, анкеритовых, анкерит-доломитовых и сидеритовых карбонатитов. Одна из последних стадий карбонатитового магматизма в массиве Салланлатва – проявление эксплозивных процессов, приведших к образованию ...